Dimethylaminomicheliolide (DMAMCL) Suppresses the Proliferation of Glioblastoma Cells via Targeting Pyruvate Kinase 2 (PKM2) and Rewiring Aerobic Glycolysis - Guo, Jianshuang; Xue, Qingqing; Liu, Kaihui; Ge, Weizhi; Liu, Wenjie; Wang, Jiyan; Zhang, Mengyi; Li, Qiu-ying; Cai, Dongpo; Shan, Changliang; Zhang, Chunze; Liu, Xinqi; et al. (Frontiers in Oncology, 2019)
Glioblastoma (GBM) is the most prevalent malignant tumor in the central nervous system. Aerobic glycolysis, featured with elevated glucose consumption and lactate production, confers selective advantages on GBM by utilizing nutrients to support rapid cell proliferation and tumor growth. Pyruvate kinase 2 (PKM2), the last rate-limiting enzyme of glycolysis, is known to regulate aerobic glycolysis, and considered as a novel cancer therapeutic target. Herein, we aim to describe the cellular functions and mechanisms of a small molecular compound dimethylaminomicheliolide (DMAMCL), which has been used in clinical trials for recurrent GBM in Australia. Our results demonstrate that DMAMCL is effective on the inhibition of GBM cell proliferation and colony formation. MCL, the active metabolic form of DMAMCL, selectively binding to monomeric PKM2 and promoting its tetramerization, was also found to improve the pyruvate kinase activity of PKM2 in GBM cells. In addition, non-targeting metabolomics analysis reveals multiple metabolites involved in glycolysis, including lactate and glucose-6-phosphate, are decreased with DMAMCL treatment. The inhibitory effects of DMAMCL are observed to decrease in GBM cells upon PKM2 depletion, further confirming the importance of PKM2 in DMAMCL sensitivity. In conclusion, the activation of PKM2 by DMAMCL results in the rewiring aerobic glycolysis, which consequently suppresses the proliferation of GBM cells. Hence, DMAMCL represents a potential PKM2-targeted therapeutic agent against GBM.